Implementing Experience Sampling Technology for Functional Analysis in Family Medicine – A Design Thinking Approach - Daniëls, Naomi E. M.; Hochstenbach, Laura M. J.; van Bokhoven, Marloes A.; Beurskens, Anna J. H. M.; Delespaul, Philippe A. E. G. (Frontiers in Psychology, 2019)
Background: A paradigm shift in healthcare from illness to wellbeing requires new assessment technologies and intervention strategies. Self-monitoring tools based on the Experience Sampling Method might provide a solution. The PsyMate™ is an experience-sampling platform that enables patients to monitor both vulnerability and resilience in daily life. Although the PsyMate™ is extensively used in research, a translation from science into daily clinical practice is needed. Objective: To investigate the redesign process of the PsyMate™ for detailed functional analysis and disease management used by psychological wellbeing practitioners in family medicine. Methods: The PsyMate™ was reconceptualized according to the design thinking framework in three phases. Psychological wellbeing practitioners were closely involved in co-creation sessions. In the ‘understand’ phase, knowledge about end-users’ characteristics and current eHealth use was collected (nominal group technique – 2 sessions with N=15). In the ‘explore’ phase, key needs concerning the PsyMate™ content and functionalities were evaluated and prioritized (empathy mapping – 1 session with N=5, moderated user testing – 1 session with N=4). In the ‘materialize’ phase, the adjusted version of the PsyMate™ was tested in daily clinical practice (4 months with N=4). The whole process was extensively logged, analyzed using content analysis, and discussed with an interprofessional project group. Results: In the ‘understand’ phase, psychological wellbeing practitioners emphasized the variability in symptoms reported by patients. Therefore, moment-to-moment assessment of mood and behavior in a daily life context could be valuable. In the ‘explore’ phase, (motivational) functionalities, technological performance and instructions turned out to be important user requirements and could be improved. In the ‘materialize’ phase, psychological wellbeing practitioners encountered barriers to implement the PsyMate™ at the facilitation level by the regional primary care group and general practitioners (inner setting) and the priority and motivation they gave it (individual). Conclusions: The redesign process in co-creation yielded meaningful insights into the needs, desires and daily routines in family medicine. The actual implementation in this setting turned out to be challenging. Adjustments are required on the intervention, the inner setting, and the individual level. Future research should focus on the applicability of PsyMate™ in family medicine and incorporate patient experiences.